ROLE OF MELATONIN IN THE MANAGEMENT OF SLEEP DISORDERS IN SCHIZOPHRENIA: A LITERATURE REVIEW - Andrzej Wydrych,; Patryk Pindlowski,; Ewa Wietrzykowska,; Piotr Trojan,; Maja Kuklo,; Aleksandra Karolak,; Agata Karasiewicz,; Marta Kras,; Aleksandra Tomczyk,; Michał Olkowski, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: Sleep and circadian rhythm disturbances are highly prevalent in Schizophrenia and significantly impact symptom severity, disease progression, and treatment outcomes. Schizophrenia, a chronic and disabling mental illness affecting approximately 1% of the global population, is particularly associated with pronounced sleep abnormalities. Over 80% of patients with schizophrenia experience reduced sleep efficiency and delayed sleep onset. These disturbances are closely linked to worsening psychotic symptoms, cognitive dysfunction, and diminished quality of life. This review aims to explore the role of melatonin in these disruptions and its potential as an adjunctive treatment in Schizophrenia.Materials and methods: Articles in PubMed, GoogleScholar, ScienceDirect databases were retrieved by the authors. The authors searched with keywords: melatonin, schizophrenia, sleep disorder, circadian rhythms, psychiatric disease. Articles between 2000 and 2024 were included.Results: Randomized controlled trials show that prolonged-release melatonin (2–10 mg, 1–2 hours before bedtime) improves sleep latency, efficiency, and duration in schizophrenia. Melatonin, immediate-release, has variable findings; low doses (